2016
DOI: 10.1051/matecconf/20179001050
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanolubricant automotive air conditioning (AAC) test rig

Abstract: Abstract. Nanolubricant been introduced in compressor might improve the performance of automotive air conditioning system. Prior testing of the nanolubricant enhancement performance, an automotive air conditioning (AAC) system test rig base on compact car has to be developed; therefore this paper presented the development process of AAC test rig. There are 15 thermocouples, 2 pressure gauges and power analyzer were assembled on the system in order to analyse its performance. The experiment was conducted with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Striking an optimal balance between achieving the desired cooling performance and maintaining an acceptable level of energy efficiency becomes a primary goal. This aligns with the findings of previous studies by Redhwan, Azmi, Sharif and Hagos [10] and Sharif, Azmi, Zawawi and Ghazali [5], further validating the importance of these considerations. The optimal operating point for maximizing cooling capacity while maintaining an acceptable coefficient of performance (COP) in the automotive air conditioning system is achieved when employing the R1234yf's refrigerant at a weight range of 220 to 240 kg.…”
Section: Resultssupporting
confidence: 91%
“…Striking an optimal balance between achieving the desired cooling performance and maintaining an acceptable level of energy efficiency becomes a primary goal. This aligns with the findings of previous studies by Redhwan, Azmi, Sharif and Hagos [10] and Sharif, Azmi, Zawawi and Ghazali [5], further validating the importance of these considerations. The optimal operating point for maximizing cooling capacity while maintaining an acceptable coefficient of performance (COP) in the automotive air conditioning system is achieved when employing the R1234yf's refrigerant at a weight range of 220 to 240 kg.…”
Section: Resultssupporting
confidence: 91%
“…A nanofluid is generally understood to mean a suspension of nano-sized particles having diameter of about 1 nm to 100 nm in a conventional base fluid [2][3][4]. The beauty of nanofluid is that it can improve or enhance thermo-physical properties such as thermal conductivity, thermal diffusivity, viscosity and convective heat transfer coefficient [5][6][7][8][9][10]. Nanofluids are generally classified into two categories, namely metallic nanofluids (aluminium, copper, nickel, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Fluids having this combination of features are not in existence until the advent of nanofluids. Through the invention of nano-coolants, nanofluid technology contributes to a more energy-efficient and cost-effective process [5][6][7][8][9]. These nanofluids can be used in a wide range of industrial applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…For the past two decades, promising results in experimental and theoretical studies in the literature reviews have shown that nanofluids have an extensive range of potential applications for heat transfer systems such as in automobile radiators [21], refrigerators [6,22,23], solar collectors [24], mini channels [25] and electronics [26]. However, only a few studies of electronic coolants using nanofluids have been established as being related to CPU cooling [27].…”
Section: Introductionmentioning
confidence: 99%